2022
DOI: 10.1155/2022/1152463
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Taste Receptors in the Oro-Sensory Perception of Nutrients in Rainbow Trout (Oncorhynchus mykiss) Fed Diets with Different Fatty Acid Profiles

Abstract: Taste perception plays an important role in an animal’s detection of nutrients, conveying key dietary information, fundamental for its growth and survival. Because alternative terrestrial ingredients are known to affect the feeding of rainbow trout (RT, Oncorhynchus mikyss), we aimed to assess the importance of taste receptors in detection. Using self-feeders, we examined the feeding behavior (30 days of a feeding trial followed by 10 days of a preference trial) of RT fed with a commercial diet (C), vegetable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In our study, the major difference in terms of nutrients was DHA (26.53%) present in FO of the C diet and replaced by alpha-linolenic acid (ALA; 28.24%) in the V diet. As we recently suggested for the gustatory system [15], the difference in the proportion of ω-3 PUFAs between the two dietary treatments could involve the regulation of olfactory sensing receptors influencing the feeding behavior of RT. In this study, some olfactory receptor-encoding genes display modulation of their expression regarding diet and/or feeding status and are found in the three main olfactory receptor families.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study, the major difference in terms of nutrients was DHA (26.53%) present in FO of the C diet and replaced by alpha-linolenic acid (ALA; 28.24%) in the V diet. As we recently suggested for the gustatory system [15], the difference in the proportion of ω-3 PUFAs between the two dietary treatments could involve the regulation of olfactory sensing receptors influencing the feeding behavior of RT. In this study, some olfactory receptor-encoding genes display modulation of their expression regarding diet and/or feeding status and are found in the three main olfactory receptor families.…”
Section: Discussionmentioning
confidence: 81%
“…For the gustatory sensing system, our previous research assessed the detection and modulation of taste receptors in RT fed with a total plant based-diet, with or without supplementation by ω-3 LC-PUFA [15]. The results of this study showed that RT have the fundamental mechanisms for oro-gustatory perception of nutrients related to different diet composition.…”
Section: Discussionmentioning
confidence: 85%
“…We postulate that the fish underwent adaptations to accommodate the provided diet, or alternatively, the juvenile fish were compelled to consume it in order to ensure their survival. In a recent study that included a similar formulation, we demonstrated that from the juvenile stage, RT had no preference for a commercial (with DHA and EPA) or plant-based (with ALA but without DHA and EPA) diet using a self-feeder method (17) . Thus, we were interested in the postprandial regulation of FI in RT fed the V diet over the long term.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, beyond a purely neuropeptide regulation, the influence of FI could be related more to hedonic sensations of the diet. A previous study based on the same trial (17) indicated that changes in the FI of the V diet are related to a decrease in desire to eat rather than changes in the mechanisms of FI (i.e. regulation of appetite neuropeptide).…”
Section: Discussionmentioning
confidence: 95%
“…Compared to 18 s and actin , the elongation factor 1α gene ( eef1α ) showed the most stable expression between brain areas and tissues and was chosen as the reference gene. Relative expression of the target genes was determined by the ΔΔCT method [ 35 , 36 , 37 ]. Mean ± standard error of mean values for each group are expressed in fold changes relative to the BE treatment for all genes.…”
Section: Methodsmentioning
confidence: 99%